Predictive factors of melanoma thickness - Ana Rita Carreiro Silva; Ricardo José David Costa Vieira (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Melanoma thickness is a relevant prognostic marker that is crucial for staging and its calculation relies on the histopathological examination. There is a risk of thickness underestimation with an incisional biopsy if the latter is not performed on a tumor area where the thickness is maximal. This occurrence may have an impact on a therapeutic decision, particularly regarding the excision margins and the need for sentinel lymph node biopsy. Objective: To assess the association between melanoma thickness and dermoscopic, demographic, epidemiological and clinical variables, aiming to identify predictive factors of thickness >1 mm. Methods: This was an observational and cross-sectional study, carried out on patients diagnosed with melanoma, from a single center over a time span of four years. Anatomopathological (thickness), dermoscopic, demographic, epidemiological, and clinical variables were collected. The associations between the variables with melanoma thickness were assessed. Results: A total of 119 patients were included. The presence of atypical vessels on the dermoscopic examination was an independent predictive factor of thickness >1 mm. Conversely, an atypical reticular pattern predicted melanoma thickness <1 mm. The presence of ephelides and a previous history of sunburn were also associated with melanomas thinner than 1 mm in the univariate analysis. Study limitations: The lack of data related to some variables and the absence of an optimal correlation between the dermoscopic and the anatomopathological examination constituted study limitations. Conclusion: An atypical vascular pattern on dermoscopy is associated with thickness >1 mm, helping with the choice of the optimal site to perform an incisional biopsy when an excisional biopsy is not feasible.